(untitled) (Heteroglossia – studia kulturoznawczo-filologiczne, 2017)
The article discusses using several semiotic terms with their reference to linguistics and translation studies. These key terms include ‘discourse’ and ‘text’. The article highlights interconnection of three types of discourses, namely, of the author, of the translator and, as a result of this interaction, creation of the third one which is made based on the first two. The article also suggests that cultural background and ‘the picture of the world’ contributes to making up the described discourses. The present paper is aimed at expanding the theoretical base of the students-translators, making them familiar with semiotic researches in the field of discourse and text, and, what is especially important, the possibilities of applying this knowledge in the practice of translation and interpretation.